2007
DOI: 10.1016/j.oraloncology.2006.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Fine deletion mapping of chromosome 2q21-37 shows three preferentially deleted regions in oral cancer

Abstract: We analysed the loss of heterozygosity (LOH) of long arm of chromosome 2 by using 16 polymorphic microsatellite markers in 39 matched oral normal and cancer tissues, and defined the deletional mapping of the region with putative tumor suppressor genes. LOH was detected at least one location in 33 of 39 (85%) tumor tissues. Frequent deletions were detected at the locations of microsatellite markers, D2S2304 (35%), D2S111 (40%), D2S155 (35%), D2S1327 (29%), D2S164 (29%), D2S125 (68%) and D2S140 (32%). Three pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 23 publications
3
53
0
Order By: Relevance
“…Similarly, we and other groups reported chromosomal deletion and/or decrease of ING4 expression in head and neck cancers 21) , glioma 62) and breast cancer 63) . Regarding with ING5, we detected allelic loss 64) , tumor-specific mutation and for growth inhibition 67) . Previous studies have likewise implicated …”
Section: Deregulation Of Ing Family Genes In Tumorsmentioning
confidence: 86%
“…Similarly, we and other groups reported chromosomal deletion and/or decrease of ING4 expression in head and neck cancers 21) , glioma 62) and breast cancer 63) . Regarding with ING5, we detected allelic loss 64) , tumor-specific mutation and for growth inhibition 67) . Previous studies have likewise implicated …”
Section: Deregulation Of Ing Family Genes In Tumorsmentioning
confidence: 86%
“…20q13.3, frequently overexpressed in ovarian cancers, has been recently shown to localize the BRK tyrosine kinase gene (GeneID: 5753), which is thought to have an important role in the development of ovarian cancers. 16 Losses occurring at chromosome 2q have been described for various carcinomas, including head and neck squamous cell carcinoma, [17][18][19] breast carcinoma, 20 lung carcinoma, 21 neuroblastoma, 22 cervical cancer, 23 and prostate adenocarcinoma. 24 Studies using different approaches have increasingly shown that the most affected region is 2q32-q37.…”
Section: Discussionmentioning
confidence: 99%
“…Three olfactory neuroblastomas were studied by Riazimand et al 5 using conventional CGH, and amplification of whole chromosome 19, partial gains of 1p, 8q, 15q, and 22q, and deletions of 4q and 6p were detected. Szymas et al 6 studied a single olfactory neuroblastoma and found gains of whole chromosomes 4,8,11, and 14, partial gains of 1q and 17q, partial deletions of 5q and 17q, and whole chromosome losses of 16,18,19, and X. In our study, we applied for the first time an oligonucleotide-based array CGH (aCGH) to identify the most frequently occurring DNA copy number changes in 13 cases of olfactory neuroblastoma.…”
mentioning
confidence: 87%
“…We demonstrated a high ratio of LOH in oral cancer using 16 microsatellite markers on the long arm of chromosome 2q21-37.3 [24]. ING5 appeared to be a strong candidate tumor suppressor in this study though several other candidate TSGs including ILKAP, HDAC4, PPP1R7, DTYMK, STK25, BOK are also localized at the area, where frequent deletion has been detected [11,12,24]. Moreover, our recent study revealed decreased expression of ING5 mRNA and mutations in oral cancer samples as compared to their corresponding normal controls, suggesting its tumor suppressive role in cancer [25].…”
Section: Abnormalities Of Ing Family Genes In Head and Neck Cancermentioning
confidence: 89%
“…Our continuous efforts led to identification of ING3 [14]. Following these works, other groups and our group published investigations on other members of ING family including ING2, ING4 and ING5 [15,16,[24][25][26][27][28][29][30][31][32]. Although almost all of the ING family members are known to be negative regulator of the cell growth, recent studies also demonstrated some of the members or splicing variants also functioning as oncogene, thus complicating the role of these genes in human carcinogenesis [31,32].…”
Section: Introductionmentioning
confidence: 99%